The Synthesis and Characterisation of Hydroxypropyl Cyclodextrin Inclusion Complexes in Certain Medications and Fluorophores are Compared (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Pharmaceutical and biochemical researchers have shown great interest in the development and study of hydroxypropyl cyclodextrin (HP-β-CD) inclusion complexes because of their potential to improve the solubility, stability, and bioavailability of different drugs and fluorophores that are not very water-soluble. This research compares the methods of synthesis, efficiency of encapsulation, and physical and chemical characteristics of HP-β-CD inclusion complexes made with various drugs and fluorophores. We synthesised inclusion complexes using kneading, freeze-drying, and co-precipitation procedures. Then, we characterised them using spectroscopic methods including FTIR, NMR, and UV-Vis, as well as thermal (DSC, TGA), and crystallographic (XRD) investigations. The effective encapsulation was confirmed by the creation of inclusion complexes, which resulted in notable alterations in spectral patterns, thermal stability, and crystalline structure. Complexation with fluorophores increased photostability and fluorescence intensity, whereas medications exhibited higher water solubility and regulated release behaviour. While the inclusion method stays the same (via non-covalent contacts within the hydrophobic cavity of HP-β-CD), the comparison analysis shows that the guest molecule's structural structure and polarity determine the level of complexation and functional enhancement. These results highlight the flexible use of HP-β-CD as a host molecule in drug delivery systems and fluorescence applications, which bodes well for its potential in pharmaceutical and biomedical formulations.